Comparison of methods for diagnosis of bancroftion filariasis - Chandrasena, T.G.A.N (My University, 2000)
The objectives were firstly to evaluate a rapid format ICT card test (ICT diagnostics Australia) for filariasis in the diagnosis of bancroftain filariasis and to compare its sensitivity, specificity and cost effectiveness with TBF ( standard survey tool) and secondly to investigate any association between antigenaemia, microfilaraemia and clinical manifestations. As a screening tool ICT appears to be effective (both sensitive and specific) but not cost effective for routine mass surveillance in Sri Lanka. Both ICT and NMF were positive in only 40 per cent of individuals with features suggestive of clinical filariasis